Investigator-initiated clinical trials (IICTs) in Portugal: clinical investigator needs and support from clinical research infrastructure networks - Matias, Daniela Maria Sequeira (2019)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019